Basic Business Statistics / Concepts and Applications - Berenson Mark L.; Levine David M (Prentice Hall International, 1992)
Preface, Introduction, Data Collection, Describing and Summarizing Data, Data Presentation, Using the Computer for Descriptive Statistical Analysis, Basic Probability, Some Important Discrete Probability Distributions, The Normal Distribution, Sampling Distributions, Estimation, Hypothesis Testing I: Introduction and Concepts, Hypothesis Testing II: Differences Between Quantitative Variables, Hypothesis Testing III: Differences Between Proportions and Other Chi-Square Tests, The Analysis of Variance, Nonparametric Methods, The Simple Linear Regression Model and Correlation, Multiple Regression Models, Index Numbers and Time Series and Business Forecasting, Statistical Applications in Quality and Productivity Management, Answers to Selected Problems, Appendices, Index.